Peer Tutoring as A Best Practice of Accounting Learning in Vocational Education - Mika Marsely (Universitas Negeri Malang, 2020)
This study attempts to investigate the use of peer tutoring and to assest the effectiveness of peer tutoring in accounting learning, State Polytechnic of Malang. A descriptive research approach with case study was employed in this research. The information gathered by documentation, observation and in depth interview. The accounting learning was done by the author with apllying same age peer tutoring (co-peer). The findings revealed that peer tutoring is a very effective learning strategy both to tutors and tutees. Tutors feels happy, proud, and satisfied when the lecturers trust them to give the material in front of their friends. Whereas the tutees feel more comfortable because the learning activities has become more relaxed and not strained, the students have been brave to ask more question. Peer tutoring has improve the academic achievement, communication skill, responsibilities, patience, empathy, sympathy, and strengthening the social skills both to tutors and tutees. As we know that these all skills were very needed in the world life. The author suggest that it should be utilized within the premises of the educational institutions. It is a must for polytechnic students to be equipped with such ability given that it has a great impact towards their future career development. The graduates are believed to be able to perform productively in the society with this ability, notwithstanding what contexts they are in. This is to assure that they would be able to function in line with the complex world of today.